2021
DOI: 10.1200/jco.2021.39.15_suppl.4062
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of KN046 plus paclitaxel/cisplatin as first-line treatment for unresectable locally advanced, recurrent or metastatic esophageal squamous cell carcinoma (ESCC).

Abstract: 4062 Background: The prognosis of pts with advanced esophageal squamous cell carcinoma (ESCC) remains dismal clinically. Paclitaxel and cisplatin were used as the standard first-line regimen in ESCC for almost two decades. Recently, the combination of PD-1/PD-L1 pathway blockades with chemotherapy has shown synergistic efficacy in a few clinical trials. KN046 is the world's first dual immune checkpoint inhibitor, which can block PD-1/PD-L1 and CTLA-4 pathways at the same time. The purpose of this ongoing phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Erfonrilimab is a symmetric full-length IgG1 PD-1×CTLA-4 bsAb. Combined with chemotherapy, erfonrilimab induced ORRs of 50.6%, 58.3%, and 55.6% in NSCLC, 390 ESCC, 391 and PDAC patients. 392 A similar ORR of 57% was also observed combining erfonrilimab and lenvatinib in HCC patients.…”
Section: Immunoregulatory Bispecific and Multi-specific Antibodiesmentioning
confidence: 99%
“…Erfonrilimab is a symmetric full-length IgG1 PD-1×CTLA-4 bsAb. Combined with chemotherapy, erfonrilimab induced ORRs of 50.6%, 58.3%, and 55.6% in NSCLC, 390 ESCC, 391 and PDAC patients. 392 A similar ORR of 57% was also observed combining erfonrilimab and lenvatinib in HCC patients.…”
Section: Immunoregulatory Bispecific and Multi-specific Antibodiesmentioning
confidence: 99%
“… 256 A phase II KN046-204 trial (NCT03925870) of KN046 monotherapy or combined with chemotherapy in ESCC is ongoing, in which the ORR and DCR are 58.3% and 91.6%, respectively, in a cohort with KN046 plus first-line chemotherapy. 150 The treatment efficacy of a fully human immunoglobin G4 anti-PD-L1 mAb sugemalimab (CS1001) in combination with first-line chemotherapy is also assessing in a phase III trial (NCT04187352) ( Table 6 ).…”
Section: Potent Molecular-targeted Therapy For Patients With Esccmentioning
confidence: 99%
“…The first-inhuman study has demonstrated that KN046 monotherapy has an acceptable safety profile and is in line with previously reported safety data from other ICIs, and the preliminary efficacy results are promising 9 . Several clinical trials of KN046 monotherapy and combination therapy were conducted in different advanced solid tumors, including non-small cell lung cancer (NSCLC), hepatocellular carcinoma (HCC), pancreatic cancer, esophageal squamous cell carcinoma, and rare thoracic tumors, which have shown promising efficacy and well-tolerated toxicity [10][11][12][13][14] .…”
mentioning
confidence: 99%